Understanding Recidivism: An Analysis of Demographic Factors, Crime Types, and Release Mechanisms in the Context of Recidivism in New Hampshire (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2024)
This study explores recidivism patterns in New Hampshire, examining how demographic factors, crime types, and release mechanisms influence outcomes for formerly incarcerated individuals. The findings highlight that recidivism is most prevalent among younger adults, particularly within the first 12 months post-release, with age, gender, and racial disparities contributing to these trends. Notably, Black and Hispanic populations, as well as individuals convicted of drug-related and violent crimes, exhibit higher recidivism rates, often facing compounded socio-economic challenges. Parole release mechanisms also emerge as significant, with technical violations—especially among low-income, young, or minority parolees—frequently resulting in re-incarceration. Addressing these dynamics requires targeted interventions, such as flexible parole conditions and accessible support for substance use and mental health, aimed at reducing repeat offenses and promoting sustainable reintegration. These insights underscore the need for equitable, community-based alternatives to traditional punitive measures, ultimately supporting a fairer and more effective approach to criminal justice in New Hampshire.